MRI-guided intrathecal transplantation of hydrogel-embedded glial progenitors in large animals - Malysz-Cymborska, Izabela; Golubczyk, Dominika; Kalkowski, Lukasz; Burczyk, Adam; Janowski, Miroslaw; Holak, Piotr; Olbrych, Katarzyna; Sanford, Joanna; Stachowiak, Kalina; Milewska, Kamila; Gorecki, Przemysław; Adamiak, Zbigniew; et al. (Scientific reports, 2018)
Disseminated diseases of the central nervous system such as amyotrophic lateral sclerosis (ALS) require that therapeutic agents are delivered and distributed broadly. Intrathecal route is attractive in that respect, but to date there was no methodology available allowing for optimization of this technique to assure safety and efficacy in a clinically relevant setting. Here, we report on interventional, MRI-guided approach for delivery of hydrogel-embedded glial progenitor cells facilitating cell placement over extended surface of the spinal cord in pigs and in naturally occurring ALS-like disease in dogs. Glial progenitors used as therapeutic agent were embedded in injectable hyaluronic acid-based hydrogel to support their survival and prevent sedimentation or removal. Intrathecal space was reached through lumbar puncture and the catheter was advanced under X-ray guidance to the cervical part of the spine. Animals were then transferred to MRI suite for MRI-guided injection. Interventional and follow-up MRI as well as histopathology demonstrated successful and predictable placement of embedded cells and safety of the procedure.